2013
DOI: 10.1038/ejcn.2013.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quercetin on P-glycoprotein transport ability in Chinese healthy subjects

Abstract: Quercetin significantly induced the activity of P-gp and this induced effect was more obvious in MDR1 3435 TT individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 33 publications
(32 reference statements)
3
32
0
Order By: Relevance
“…The effect of quercetin on P-gp seems to be dual in nature. On the one hand, the study by Wang et al demonstrated a 20% reduction in talinolol exposure when coadministered with quercetin, which suggests P-gp induction by quercetin [86]. Furthermore, quercetin decreased the exposure of cyclosporine by 43.3% in rats [103].…”
Section: Quercetinmentioning
confidence: 98%
“…The effect of quercetin on P-gp seems to be dual in nature. On the one hand, the study by Wang et al demonstrated a 20% reduction in talinolol exposure when coadministered with quercetin, which suggests P-gp induction by quercetin [86]. Furthermore, quercetin decreased the exposure of cyclosporine by 43.3% in rats [103].…”
Section: Quercetinmentioning
confidence: 98%
“…Such processes would be expected to become more likely with increasing duration of quercetin exposure. Quercetin may also have a different impact on certain genotypes, e.g., encoding for P‐glycoprotein (possibly via multi‐drug resistance gene induction) which could be also associated with an altered drug level . In addition, an inhibition of the organic anion‐transporting polypeptide 1B1 by quercetin has also been suggested .…”
Section: Safety Aspectsmentioning
confidence: 99%
“…Even its extremely high-dietary intake can result in only nanomolar concentrations of total quercetin (the parent compound and its metabolites) in the circulation (Kelly, 2011); however, administration of dietary supplements with high-quercetin content (e.g., 500-1,000-mg aglycone in a single tablet/capsule) leads to micromolar plasma concentrations of total quercetin (Conquer, Maiani, Azzini, Raguzzini, & Holub, 1998;Heinz et al, 2010). In addition to its potential pharmacodynamic effects, quercetin can interact with serum albumin (causing displacement of drugs from albumin; Poór et al, 2013), cytochrome P450 (CYP) enzymes (Kimura, Ito, Ohnishi, & Hatano, 2010), and transport proteins (Wang et al, 2013). These effects may be responsible for pharmacokinetic interaction between quercetin and medications (Poór et al, 2017;Srinivas, 2015).…”
mentioning
confidence: 99%